LAPAROSCOPIC SPLEENECTOMY AS A METHOD OF CHOICE IN SURGICAL TREATMENT OF BLOOD SYSTEM DISEASE PATIENTS - Khvorostov, E.D.; Semenenko, I.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The results of surgical treatment of 14 patients (12 – with blood system diseases, 2 patients with nonparasitic cysts of spleen) were analyzed in the article. The questions of indications to surgical treatment of blood system disease patients and principles of rational transfusion tactics were considered. The methods of laparoscopic spleenectomy, which had been used in the surgical department of Railway clinical hospital of Kharkov since July, 2000, were described and applied in practice. A comparative evaluation of advantages and usage advisability of laparoscopic method use is carried out. Special consideration was given to establishment of indications to splenectomy, preoperative preparation and conducting of postoperative period of. Authors showed, that spleenectomy of blood system disease patients related to operation with increased risk, though laparoscopic spleenectomy that required corresponding experience of a surgeon and technical equipment, was an alternative to open spleenectomy.